КРАТКИЙ ОБЗОР ДЕЯТЕЛЬНОСТИ МУХАММЕДА ХАДИ ДО ВСТУПЛЕНИЯ В МИР ПРЕССЫ И ЛИТЕРАТУРЫ - Гарибли, И. (Journal of Oriental Studies, 2016)
Тарихи дереккөздерде ХХ ғасырдың алғашқы онжылдығы шығыс елдерінде ояну, өзін-өзі тану, ұлт-азаттық қозғалыс кезеңі ретінде сипатталады. МақаладаМ. Хадидің әдебиет пен баспасөз әлеміне өткенге дейін-гі шығармашылығына қысқа шолу жасалған.The article overviews the period until Hady’s coming toliterature and art world. It explores the environment inwhich the poet was born and rose. The article givesinformation about the poet’s family tree, his childhood andearly youth years. It examines the causes that facilitatedHady’s growing up as a personality ad artist in a provincialcity like Shamakhi.